Assessment of Malondialdehyde as a Biomarker of Oxidative Stress and Its Correlation with 25-hydroxy Vitamin D3 in Women with Polycystic Ovary Syndromeoxy Vitamin D3 - Qasim , Mohammed N.; Mahmood , Halla Gh. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Polycystic Ovary Syndrome (PCOS) is a prevalent endocrinology disorder affecting women in the years of reproduction. Malondialdehyde (MDA) is a result of polyunsaturated fatty acid peroxidation and is widely utilized as a trustworthy indicator of peroxidation of lipids and oxidative damage. Conversely, Vitamin D deficiency is a global issue affecting around one billion individuals. 25-hydroxyvitamin D₃ is linked to multiple metabolic processes and reproduction facets of women with PCOS and thus may contribute to the PCOS pathophysiology.Objectives: To measure and compare serum malondialdehyde levels and 25-hydroxyvitamin D₃ concentrations between women with polycystic ovary syndrome (PCOS) versus age-matched healthy controls and to investigate the correlation between malondialdehyde and 25-hydroxyvitamin D₃ levels in both groups to elucidate potential mechanistic links between oxidative stress and vitamin D deficiency in PCOS pathophysiology.Methods: The present case-control research was conducted at the Infertility Centre of Al-Batool Teaching Hospital, Diyala Governorate, Iraq, in collaboration with the Biochemistry Department at the College of Medicine, University of Baghdad, from April 2024 to January 2025. A total of 132 women aged 18-40 years were included in this study, comprising 66 PCOS cases and 66 healthy controls. A competitive enzyme-linked immunosorbent assay assessed the concentrations of serum malondialdehyde and 25-hydroxy vitamin D3.Results: The results indicated markedly elevated serum malondialdehyde concentrations within the PCOS group compared to the controls. The concentrations of 25-hydroxy vitamin D3 in the PCOS group were considerably reduced compared to the controls. A significant negative correlation was found between serum malondialdehyde levels and 25-hydroxy vitamin D3  in the PCOS Group.Conclusion: The current study showed that PCOS cases had much higher MDA levels than controls, probably indicating that they have experienced more oxidative stress. The level of 25(OH)D showed a common lack of this vitamin in the PCOS cases.